Analysis of the turbulent wind above and within a fir forest - Scarabino, Ana Elena (2001)
In this work wind data from the measuring tower in the Solling fir forest at Goettingen, Germany, are processed and analyzed. Wind records are supplied by the Institute of Bioclimatology at the Georg Augustus University. An attempt is made to identify some of the vortical structures at the upper shear layer, and to study their penetration into the lower atmosphere within the forest and the interaction with the low velocity flow at this region. Analysis of anemometrical data suggests two types of phenomena coexisting in the upper mixing layer region of the flow: large-scale roughness-type independent phenomena, and structures of frequent penetration with smaller length scales, related to vertical transport processes.